Factors affecting negative and positive emotions among spouses caring for patients with psychotic or bipolar disorder - Haruka Ogawa; Nao Shiraishi; Hiroko Yatsu; Tatsuo Akechi (PCN Reports)
Abstract Aim Spouses experience conflicting emotions when caring for partners with severe mental illnesses. They can have negative emotions while also regarding caregiving as positive and may develop a better marital relationship through the caregiving process. This study investigated factors affecting the negative and positive emotions of husbands and wives acting as caregivers of their spouses with severe mental illnesses. Methods An online nationwide survey of 166 spouses caring for partners diagnosed with schizophrenia, schizoaffective disorder, or bipolar disorder was conducted. Caregivers' negative and positive emotions, personal and role strains in the care burden, sense of coherence, and patients' disabilities in family communication were assessed. We conducted a series of hierarchical multiple regression analyses to evaluate the effects of these factors on the emotions of husbands and wives separately. Results Among the 166 spouses, 112 (67%) were husbands and 54 (33%) were wives. Husbands were caregivers to 1.4 times as many individuals diagnosed with psychotic disorder as were wives. The negative emotions of husbands were linked to personal strain, whereas those of wives were associated with patient disability in family communication. Sense of coherence was the only factor predicting positive emotions for both sexes. Conclusion Support for spousal caregivers should be adjusted according to sex. A reduction in husbands' personal strain can alleviate their negative emotions, whereas wives' negative emotions can be relieved by improving communication within their families. Regardless of sex, a higher sense of coherence level has the potential to suppress negative emotions and enhance positive emotions.